The Influence of Total Quality Management (TQM), Reward Systems, and Performance Measurement Systems on Company Performance through Employee Productive Behavior As Mediation Variables in Garment Companies - Hartono Hartono; Toto Heru Dwihandoko; Mohammad Muslimin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
Today’s business world has experienced rapid development. There is intense competition among fellow companies. The management system can work as a tool to improve company performance by measuring its employees’ performance. A performance measuring system is required to improve business performance. It will later function as an information provider that can be a reference for managers in making correct decisions for the company’s progress in general. This study focuses on garment companies using SEM PLS data analysis techniques, producing different results. It uses a quantitative descriptive method. It looks at the company’s performance measurement only from a financial point of view. The result showed that there is a significant beneficial impact between the TQM, employee productive behavior on company performance, and TQM on employee productive behavior. However, there is no effect of the reward system on the company’s performance. The productive behavior of employees can mediate the reward system based on company performance. Performance measurement systems can be mediated by productive employee behavior upon company performance. Employees that engage in productive behavior can mediate TQM on mediated company performance. The suggestion of the result of this research is the company can consider these research results to develop their company performance to achieve their goal. Therefore, the researchers also suggest that others conduct further research using a different method and variables that have not been studied in this study.